Greetings as social action in Finland Swedish and Sweden Swedish service encounters – a pluricentric perspective - Jenny Nilsson; Stefan Norrthon; Jan Lindström; Camilla Wide (De Gruyter, 2022)
While greetings are performed in all cultures and open most conversations, previous studies suggest that there are cross-cultural differences between different languages in greeting behavior. But do speakers of different national varieties of the same language organize and perform their greeting behavior in similar ways? In this study, we investigate the sequential organization of greetings in relation to gaze behavior in the two national varieties of wedish: Sweden Swedish spoken in Sweden and Finland Swedish spoken in Finland. In recent years, the importance of studying pluricentric languages from a pragmatic perspective has been foregrounded, not least within the framework of variational pragmatics. To date, most studies have focused on structural differences between national varieties of pluricentric languages. With this study, we extend the scope of variational pragmatics through adding an interactional, micro perspective to the broader macro analysis typical of this field. For this study, we have analyzed patterns for greetings in 297 videorecorded service encounters, where staff and customers interact at theatre box offices and event booking venues in Sweden and Finland. The study shows that there are similarities and differences in greeting behavior between varieties. There is a strong preference for exchanging reciprocal verbal greetings, one at a time, in both. There is also a similar organization of the greeting sequence, where customer and staff establish mutual gaze prior to the verbal greetings, thus signaling availability for interaction. The duration of mutual gaze and the timing of the greeting, however, differ between the two varieties. We have also conducted a multi modal analysis of gaze behavior in correlation to the greeting. We found that the customers and staff in the Finland Swedish data share mutual gaze before and during the verbal greeting, and often avert gaze after the verbal greetings. However, in the Sweden Swedish data, the participants often avert gaze before the verbal greetings. Our results thus indicate that both similarities and differences in pragmatic routines and bodily behavior exist between the two national varieties of Swedish. The present study on greeting practices in Finland Swedish and Sweden Swedish should contribute to the field of variational pragmatics and to the development of pluricentric theory.